Сontrol of filmforming process of polymeric coverages on wooden bases - Savenets , Mykola (Forestry, Forest, Paper and Woodworking Industry, 2024)
Analysis of film forming process of thin polymeric coverages from thermoplastic and termoreactive resins on wooden bases are given. Minimization of time disproportion necessity on execution of technological finishing process operations of wooden bases, also including for counting of his abbreviation attached to drying (hardening) of polymeric films are motivated. On example of practical use of famous process intensification methods of transformation polymeric coverages from liquid into hard state with taking into account of their operational properties and physical-chemical interaction with wooden bases, are offered optimization variants of the finishing technology. Specifically, is accented attention of influence of internal efforts and phenomena of process filmforming by chemical constituents of wooden base on optimization hardening mode disposition of polymeric coverages on base termoreactive of resins. Basic stages optimization regimes of hardening with analysis of basic sides of each from stages in intercommunication with definite operational indexes protectively – decorative coverages on wooden bases are introduce. Processes research aim filmforming of polymeric coverages on wooden bases and set basic tasks, settlement of which provides her realization are formulated.